Environmental sensitivity differs between rabbit lines selected for reproductive intensity and longevity. (18th November 2013) - Savietto, D.; Cervera, C.; Blas, E.; Baselga, M.; Larsen, T.; Friggens, N. C.; Pascual, J. J.
Abstract : To better understand the mechanisms that allow some animals to sustain their productive effort in harsh environmental conditions, rabbit does from two selection lines (LP and V) were housed in normal (NC), nutritional (NF) or heat (HC) challenging environmental conditions from first to third partum. The LP line ( n =85) was founded on reproductive longevity criteria by selecting does from commercial farms that had a minimum of 25 partum with more than 7.5 kits born alive per parity. Line V ( n =79) was constituted from four specialised maternal lines into a composite synthetic line and then selected by litter size at weaning for 36 generations. Female rabbits in NC and NF environments were housed at normal room temperature (18°C to 24°C) and fed with control [11.6 MJ digestible energy (DE)/kg dry matter (DM)] or low-energy diets (9.1 MJ DE/kg DM). HC does were housed at high room temperatures (25°C to 35°C) and fed the control diet. Female rabbits in the HC and NF environments ingested 11.5% and 6% less DE than NC does, respectively ( P <0.05). These differences between environments occurred in both lines, with the differences being higher for LP than for V does (+6%; P <0.05). Milk yield responses followed those of energy intake also being higher for LP does (+21.3 g/day; P <0.05). The environmental conditions did not affect the perirenal fat thickness (PFT), but a genotype by environment interaction was observed. In NC and HC, the PFT was higher for line V (+0.23 and +0.35 mm, respectively; P <0.05) than for LP does, but this was not the case at NF (−0.01 mm). Moreover, the PFT evolution was different between them. In the NC environment, LP does used the accreted PFT in late lactation (−0.29 mm), whereas V does did not (−0.08 mm). Conversely, in the HC environment, LP does showed a flat PFT evolution in late lactation, whereas V does accumulated PFT. In the NF environment, LP and V does had a similar PFT evolution. There was also a litter size reduction for V does of −2.59 kits total born in HC and −1.78 kits total born in NF environments, whereas this was not observed for LP does. The results for LP does indicate a direct use of DE ingested for reproduction with little PFT change, whereas V does actively use the PFT reserves for reproduction.